Radio Echo Sounding investigations at Talos Dome (East Antarctica): bedrock topography and ice thickness - C. Bianchi; L. Cafarella; P. De Michelis; M. Frezzotti; A. Zirizzotti; A. Forieri; I. Tabacco (INGV, 2003)
Radio echo sounding measurements were collected during two Antarctic expeditions to determine the ice thickness and the sub-glacial morphology of Talos Dome in the region around 72°48′S; 159°06′E (about 6400 km2) on the edge of the East Antarctic plateau adjacent to Victoria Land in the western Ross Sea sector. The increasing interest in this region is due to the fact that in this area the ice accumulation is higher than in other sites in East Antarctica. Because of this, Talos Dome could be a new site for a project of a deep ice core drilling to obtain information on climate changes near the coast of Antarctica. In this frame, the knowledge of the bedrock topography is of great importance to choose the best location for the drilling site. In this paper, airborne radio echo sounding results from two Antarctic expeditions (1997 and 1999) are presented. Bedrock topography in bi- and three-dimensions for the Talos Dome region are discussed.